1
$\begingroup$

Two cones with a common vertex pass through the curves $z^2=4ax,y=0$ and $z^2=4by,x=0.$ The plane $z=0$ meets them in two conics which intersect in four concyclic points.Show that the vertex lies on the surface $z^2(\frac{x}{a}+\frac{y}{b})=4(x^2+y^2)$


Let the common vertex of the two cones is $(\alpha,\beta,\gamma)$ and let the direction cosines of the generator line of first cone which passes through $z^2=4ax,y=0$ be $l_1,m_1,n_1$ and the direction cosines of the generator line of second cone which passes through $z^2=4ay,x=0$ be $l_2,m_2,n_2.$

The generator line of the first cone is $\frac{x-\alpha}{l_1}=\frac{y-\beta}{m_1}=\frac{z-\gamma}{n_1}.$The equation of the first cone is $(\gamma-\frac{z\beta}{y})^2=4a(\alpha-\frac{\beta x}{y})$

The generator line of the second cone is $\frac{x-\alpha}{l_2}=\frac{y-\beta}{m_2}=\frac{z-\gamma}{n_2}.$The equation of the second cone is $(\gamma-\frac{z\alpha}{x})^2=4b(\beta-\frac{\alpha y}{x})$

I am stuck here.Please help me.

$\endgroup$
  • $\begingroup$ Can we get problem source or book? $\endgroup$ – Narasimham Jun 20 '16 at 15:46
  • $\begingroup$ books.google.co.in/… $\endgroup$ – Brahmagupta Jun 20 '16 at 16:10
  • $\begingroup$ It is question number $7.$ $\endgroup$ – Brahmagupta Jun 20 '16 at 16:11
2
+50
$\begingroup$

The generator line of the first cone is $\frac{x-\alpha}{l_1}=\frac{y-\beta}{m_1}=\frac{z-\gamma}{n_1}.$

Setting $y=0$ gives $$\frac{x-\alpha}{l_1}=\frac{0-\beta}{m_1}=\frac{z-\gamma}{n_1}\implies x=-\beta\frac{l_1}{m_1}+\alpha,\quad z=-\beta\frac{n_1}{m_1}+\gamma\tag1$$ Also, $$\frac{l_1}{m_1}=\frac{x-\alpha}{y-\beta},\quad \frac{n_1}{m_1}=\frac{z-\gamma}{y-\beta}\tag2$$ From $(1)(2)$, $$z^2=4ax\implies \left(-\beta\cdot \frac{z-\gamma}{y-\beta}+\gamma\right)^2=4a\left(-\beta\cdot\frac{x-\alpha}{y-\beta}+\alpha\right)\tag3$$

The generator line of the second cone is $\frac{x-\alpha}{l_2}=\frac{y-\beta}{m_2}=\frac{z-\gamma}{n_2}.$

Setting $x=0$ gives $$\frac{0-\alpha}{l_2}=\frac{y-\beta}{m_2}=\frac{z-\gamma}{n_2}\implies y=-\alpha\frac{m_2}{l_2}+\beta,\quad z=-\alpha\frac{n_2}{l_2}+\gamma\tag4$$

Also, $$\frac{m_2}{l_2}=\frac{y-\beta}{x-\alpha},\quad \frac{n_2}{l_2}=\frac{z-\gamma}{x-\alpha}\tag5$$ From $(4)(5)$, $$z^2=4by\implies \left(-\alpha\cdot \frac{z-\gamma}{x-\alpha}+\gamma\right)^2=4b\left(-\alpha\cdot \frac{y-\beta}{x-\alpha}+\beta\right)\tag6$$

Setting $z=0$ in $(3)(6)$ give $$\left(-\beta\cdot \frac{0-\gamma}{y-\beta}+\gamma\right)^2=4a\left(-\beta\cdot\frac{x-\alpha}{y-\beta}+\alpha\right)\implies y^2\gamma^2=4a(\alpha y-\beta x)(y-\beta)$$ $$\implies b\alpha (\gamma^2-4a\alpha) y^2+4ab\alpha \beta xy+4ab\alpha^2\beta y-4ab\alpha \beta^2 x=0\tag7$$ $$\left(-\alpha\cdot \frac{0-\gamma}{x-\alpha}+\gamma\right)^2=4b\left(-\alpha\cdot \frac{y-\beta}{x-\alpha}+\beta\right)\implies x^2\gamma^2=4b(x\beta-\alpha y)(x-\alpha)$$ $$\implies a\beta (\gamma^2-4b\beta) x^2+4ab\alpha\beta xy+4a\beta^2 b\alpha x-4ba\beta \alpha^2 y=0\tag8$$

The four intersection points of $(7)$ with $(8)$ satisfy $$b\alpha (\gamma^2-4a\alpha) y^2+4ab\alpha \beta xy+4ab\alpha^2\beta y-4ab\alpha \beta^2 x+k(a\beta (\gamma^2-4b\beta) x^2+4ab\alpha\beta xy+4a\beta^2 b\alpha x-4ba\beta \alpha^2 y)=0$$

Since it represents a circle for some $k$, we have to have $k=-1$ and $$b\alpha (\gamma^2-4a\alpha)=-a\beta (\gamma^2-4b\beta) ,$$ i.e. $$\gamma^2\left(\frac{\alpha}{a}+\frac{\beta}{b}\right)=4(\alpha^2+\beta^2)$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.